Drinking water disinfection byproducts and risk of orofacial clefts in the National Birth Defects Prevention Study. Issue 12 (13th August 2018) - Weyer, Peter; Rhoads, Anthony; Suhl, Jonathan; Luben, Thomas J.; Conway, Kristin M.; Langlois, Peter H.; Shen, Dereck; Liang, Dong; Puzhankara, Soman; Anderka, Marlene; Bell, Erin; Feldkamp, Marcia L.; et al.
Abstract: Background: Maternal exposure to drinking water disinfection byproducts (DBP)s may contribute to orofacial cleft (OFC) development, but studies are sparse and beset with limitations. Methods: Population‐based, maternal interview reports of drinking water filtration and consumption for 680 OFC cases (535 isolated) and 1826 controls were linked with DBP concentration data using maternal residential addresses and public water system monitoring data. Maternal individual‐level exposures to trihalomethanes (THM)s and haloacetic acids (HAA)s (µg/L of water consumed) were estimated from reported consumption at home, work, and school. Compared to no exposure, associations with multisource maternal exposure <1/2 or ≥1/2 the Maximum Contaminant Levels (MCL)s for total THMs (TTHM)s and HAAs (HAA5) or Maximum Contaminant Level Goals (MCLG)s for individual THMs and HAAs (if non‐zero) were estimated for all OFCs and isolated OFCs, cleft palate (CP), and cleft lip ± cleft palate (CL/P) using logistic regression analyses. Results: Compared to controls, associations were near or below unity for maternal TTHM, HAA5, and individual THM exposures with all OFCs and isolated OFCs, CP, and CL/P. Associations also were near or below unity for individual HAAs with statistically significant, inverse associations observed with each OFC outcome group except CL/P. Conclusions: This study examined associations for maternal reports of drinking water filtration and consumption and maternal DBP exposure from drinking water with OFCs in offspring. Associations observed were near or below unity and mostly nonsignificant. Continued, improved research using maternal individual‐level exposure data will be useful in better characterizing these associations.